Acefylline activates filaggrin deimination by peptidylarginine deiminases in the upper epidermis - Méchin, Marie-Claire; Cau, Laura; Galliano, Marie-Florence; Daunes-Marion, Sylvie; Poigny, Stéphane; Vidaluc, Jean-Louis; Bessou-Touya, Sandrine; Takahara, Hidenari; Serre, Guy; Duplan, Hélène; Simon, Michel (Journal of dermatological science, 2016)
•Screening of a large chemical library identified xanthines as PAD potential activators.•Deimination of human filaggrin was enhanced by caffeine, theobromine and acefylline.•Topical application of acefylline on reconstructed human epidermis improved deimination.•Acefylline is the first identified activator of PAD1 and PAD3. Peptidylarginine deiminases (PADs) catalyze deimination (or citrullination), a calcium-dependent post-translational modification involved in several physiological processes and human diseases, such as rheumatoid arthritis and cancer. Deimination of filaggrin (FLG) by PAD1 and PAD3 during the last steps of keratinocyte differentiation is a crucial event for the epidermis function and homeostasis. This allows the complete degradation of FLG, leading to the production of free amino acids and their derivatives that are essential for epidermal photoprotection and moisturizing of the stratum corneum. To increase the flux of this catabolic pathway, we searched for activators of PADs. A large chemical library was screened first in silico and then by using an automated assay based on an indirect colorimetric measurement of recombinant human PAD activity. Potential activators were then confirmed using a recombinant human FLG as a substrate, and secondly after topical application at the surface of three-dimensional reconstructed human epidermis. The data obtained after the library screening pointed to xanthine derivatives as potential PAD activators. Among seven xanthine derivatives tested at 50–300μM, caffeine, theobromine and acefylline proved to be the most potent enhancers of in vitro deimination of FLG by PAD1 and PAD3. After topical application of a gel formulation containing 3% acefylline at the surface of reconstructed epidermis, immunoblotting analysis showed an increase in the total amount of deiminated proteins, and confocal microscopy showed an enhanced deimination in the stratum corneum. This demonstrated the activation of PADs in living cells. As a PAD activator, acefylline will be useful to study the role of deimination and could be proposed to increase or correct the hydration of the cornified layers of the epidermis.